Occurrence of legacy and emerging poly- and perfluoroalkyl substances in water: A case study in Tianjin (China). (January 2022) - Li, Yuna; Niu, Zhiguang; Zhang, Ying
Abstract: Due to the water solubility and environmentally persistent properties of poly- and perfluoroalkyl substances (PFAS), the contamination of PFAS in drinking water is raising widespread concerns for their potential adverse health risks. In the present study, the behavior of PFAS from source waters to effluent water was analyzed by taking samples from three drinking water sources (Yuqiao Reservoir, Beidagang Reservoir, and Yangtze River) and effluent of several treatment processes used in one drinking water treatment plant (DWTP) of Tianjin (China), including pre-chlorination, coagulation, sand filtration, and chlorination. The range of total concentration of PFAS (∑21 PFAS) in three source water was 6.64–19.80 ng/L (Yuqiao Reservoir), 80.00–119.86 ng/L (Beidagang Reservoir), and 15.87 ng/L (Yangtze River), respectively. As for individual PFAS, PFBA (perfluorobutanoic acid) was the most abundant PFAS, followed by PFOA (perfluorooctanoic acid), PFBS (perfluorobutane sulfonate), and PFOS (perfluorooctane sulfonate), especially, 6:2 Cl-PFESA (6:2 Cl-polyflurinated ether sulfonate) was detected in all samples. During treatment, the removal rate of ∑21 PFAS was 11%, and the removal rate of long-chain PFAS such as PFNA (perfluorononanoic acid), PFOS, and PFDS (perfluorodecane sulfonate) were relatively higher than short-chain PFAS due to their hydrophobic characteristic. Besides, the influence of seasonal factor (precipitation) on the occurrence and composition characteristics of PFAS in the aquatic environment was also investigated, and the results demonstrated that precipitation affected the total concentrations of PFAS in the aquatic environment, but barely on the composition characteristics of PFAS. Furthermore, the ecological risks could be negligible based on the concentration of PFAS measured in surface water. In the meanwhile, the health risks were also assessed based on the concentration of PFAS detected in drinking water, the result indicated that the concentrations of PFAS were less than the suggested drinking water advisories. In addition, more attention should be paid to the risk caused by the frequently detected emerging PFAS such as 6:2 Cl-PFESA and HFPO-DA (hexafluoropropylene oxide-dimer acid). Graphical abstract: Image 1 Highlights: The occurrence of PFASs in different types of water in Tianjin was investigated. Conventional drinking water treatment have little impact on PFAS concentration. Emerging PFASs 6:2 Cl-PFESA and 8:2 Cl-PFESA were detected in all samples. The seasonal factor has little effect on the composition of PFASs. Risk assessment indicated the negligible risk to ecological and human health.